The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1096/fj.10-167361
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthetic small‐molecule activators of AMPK as enhancers of autophagy and amyloid‐β peptide degradation

Abstract: AMP-activated protein kinase (AMPK) is a metabolic sensor involved in intracellular energy metabolism through the control of several homeostatic mechanisms, which include autophagy and protein degradation. Recently, we reported that AMPK activation by resveratrol promotes autophagy-dependent degradation of the amyloid-β (Aβ) peptides, the core components of the cerebral senile plaques in Alzheimer's disease. To identify more potent enhancers of Aβ degradation, we screened a library of synthetic small molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(131 citation statements)
references
References 62 publications
7
122
1
1
Order By: Relevance
“…Previous studies on neurodegenerative disorders showed that the activation of AMPK in different pathological contexts has neuroprotective or deleterious outcomes in various neuronal subtypes (Mairet-Coello et al, 2013;Vingtdeux et al, 2011). The activation of AMPK was reported to increase memory dysfunction in male AβPP mice (DiTacchio et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on neurodegenerative disorders showed that the activation of AMPK in different pathological contexts has neuroprotective or deleterious outcomes in various neuronal subtypes (Mairet-Coello et al, 2013;Vingtdeux et al, 2011). The activation of AMPK was reported to increase memory dysfunction in male AβPP mice (DiTacchio et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…249 24. Thapsigargin An inhibitor of the sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase (SERCA) that inhibits autophagic sequestration through the depletion of intracellular Ca 2+ stores; 250 however, thapsigargin may also block fusion of autophagosomes with endosomes by interfering with recruitment of RAB7, resulting in autophagosome accumulation.…”
Section: Rsvasmentioning
confidence: 99%
“…Several observations demonstrate that AMPK-mediated autophagy has a cytoprotective effect in some models of neurodegenerative disease, such as Huntington's and Alzheimer's diseases, because it contributes to the removal of aggregate-prone mutant proteins and to sustaining neuronal bioenergetics, which is negatively affected under neurodegenerative-associated pro-oxidant conditions (Spencer et al, 2009;Wong and Cuervo, 2010;Underwood et al, 2010;Vingtdeux et al, 2011;Vingtdeux et al, 2010). In support of this assumption, it has been recently suggested that NO-mediated inhibition of autophagy, which is associated with AMPK dephosphorylation, gives rise to a significant increase in huntingtin-containing aggregates in neurons that express the mutant form of the protein (Sarkar et al, 2011).…”
Section: Dual Role Of Ampk In Neurodegenerative Diseasementioning
confidence: 99%